Efficacy of ICI-based treatment in advanced NSCLC patients with PD-L1≥50% who developed EGFR-TKI resistance - Li, Yujing; Jiang, Haohua; Qian, Fangfei; Chen, Ya; Zhou, Wensheng; Zhang, Yanwei; Lu, Jun; Lou, Yuqing; Han, Baohui; Zhang, Wei (Frontiers in Immunology, 2023)
Platinum-based chemotherapy is still the standard of care for Epidermal growth factor receptor (EGFR) mutated non-small cell lung cancer (NSCLC) patients after developing EGFR-TKI resistance. However, no study focusing on the role of immuno checkpoint inhibitor(ICI) based treatments for EGFR mutated NSCLC patients who carried programmed death ligand 1 (PD-L1) tumor proportion score (TPS) greater than 50% progressed after EGFR-TKI therapy. In this study, we retrospectively investigated the outcomes of ICI-based treatments for EGFR mutated NSCLC patients carried PD-L1 TPS≥50% after developing EGFR-TKI resistance and to explore the population that may benefited from ICI-based treatment. We retrospectively collected data of advanced NSCLC patients with EGFR mutations and PD-L1 TPS≥50% who have failed prior EGFR-TKI therapies without T790M mutation at Shanghai Chest Hospital between January 2018 and June 2021. Progression-free survival (PFS) and overall survival (OS) were utilized to evaluate the outcomes of this study. A total of 146 patients were included. Up to June 20th, 2022, median follow-up was 36.7 months (IQR, 12.5-44.2 months). Among the population, 66 patients (45.2%) received chemotherapy, the remaning (54.8%) received ICI-based treatment, including 56 patients(70.0%) received ICI combined with chemotherapy (IC) and 24 patients (30.0%) received ICI monotherapy (IM). Survival analysis shown that patients who received ICI-based treatment had better progress-free survival (PFS) and overall survival (OS) compared with those treated with other therapy (median PFS, 10.0 vs. 4.0 months, P＜0.001; median OS, 39.5 vs. 24.2 months, P＜0.001). What’s more, patients who treated with IC treatment had a superior survival time than those received IM treatment (median PFS, 10.3 vs. 7.0 months, P＜0.001; median OS, 41.6 vs. 32.4 months, P＜0.001). Subgroup analysis found that the PFS and OS benefit of IC was evident in all subgroups. For advanced NSCLC patients with EGFR mutations and PD-L1 TPS≥50% who have failed prior EGFR-TKI therapies without T790M mutation, ICI-based treatment could provide a more favorable survival than classical chemotherapy. What’ s more, compared with ICI monotherapy, ICI combined with chemotherapy seems to be the preferred treatment.